XperCT Sharpening Reconstruction for Cone-Beam Computed Tomography Guided Lung and Bone Interventions - Christopher M. Murphy; L. Ray Ramoso; Eric J. Monroe (Journal of Clinical Interventional Radiology ISVIR)
C-arm cone-beam computed tomography (CBCT) is a valuable tool for three-dimensional navigation and mapping in the interventional radiology suite owing to its flexible gantry positioning, real-time three-dimensional volume acquisition, and reduced contrast and radiation use. Reports of CBCT-guided bone and lung interventions are relatively infrequent, however, possibly due in part to the lack of dedicated bone and lung reconstruction algorithms and concerns regarding insufficient lesion conspicuity. Two cases of an ad hoc intraprocedural CBCT sharpening reconstruction are presented in this article.